Monitoring Progress in Citywide Sanitation - Safi, Farhad; Furlong, Claire; Luthra, Bhitush; Rohilla, Suresh Kumar; Brdjanovic, Damir (Frontiers in Environmental Science, 2022)
For over 10 years citywide sanitation plans have been developed and now citywide inclusive sanitation is being piloted globally, yet no tools exist to monitor changes in sanitation at a citywide level. This paper explores the use of Shit Flow Diagram Graphics (SFDGs) and City Service Delivery Assessments (CSDAs) to monitor changes in sanitation at a citywide level. This was done by documenting the changes in sanitation from 2015 to 2019 in Tiruchirappalli, India and developing SFDGs and CSDAs for those years. The changes in the SFDGs and CSDAs were then compared with the documented changes. The SFDGs captured all changes in service delivery that affected >1% of the population and all ofall of the interventions in the enabling environment changed in terms of appropriateness, acknowledgement or implementation was captured by the CSDAs. Therefore, units of both tools were assessed to be appropriate for monitoring purposes. Using these tools to monitor change was complex and tedious, this was improved by the development of Trend Graphs and Citywide CSDAs. This paper highlights the potential of Trend Graphs and Citywide CSDAs to monitor sanitation at a citywide level, additionally, this is the first paper to attempt to monitor changes in sanitation holistically at a citywide level.